Illicit Transport: The Oligopeptide Permease - Ames, Bruce N. (National Academy of Sciences, 1973)
The oligopeptide permease of Escherichia coli has been characterized by Payne, Gilvarg, and their colleagues. We have confirmed its existence in Salmonella typhimurium, and have isolated a series of mutants lacking the permease. We use this transport system for smuggling a histidine biosynthetic intermediate, histidinol phosphate ester, into the bacteria as its glycylglycyl derivative, Gly-Gly-histidinol phosphate. Free histidinol phosphate ester is not transported into Salmonella. Several amino-acid analogues are shown to be much more inhibitory to Salmonella when presented to the bacteria in the form of tripeptides than as the free amino acids. The implications of this work for practical purposes are discussed. The synthesis of Gly-Gly-histidinol phosphate is described.